2009
DOI: 10.1146/annurev.pathol.4.110807.092205
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepcidin and Iron-Overload Disease

Abstract: Hepcidin, a 25-amino-acid antimicrobial peptide, is the central regulator of iron homeostasis. Hepcidin transcription is upregulated by inflammatory cytokines, iron, and bone morphogenetic proteins and is downregulated by iron deficiency, ineffective erythropoiesis, and hypoxia. The iron transporter ferroportin is the cognate receptor of hepcidin and is destroyed as a result of interaction with the peptide. Except for inherited defects of ferroportin and hepcidin itself, all forms of iron-storage disease appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
0
5

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 133 publications
1
147
0
5
Order By: Relevance
“…However, because protein-level inhibition of ferroportin is linked to high mRNA expression of hepcidin (36), and hepcidin is expressed in breast cells (Fig. 1 and fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, because protein-level inhibition of ferroportin is linked to high mRNA expression of hepcidin (36), and hepcidin is expressed in breast cells (Fig. 1 and fig.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of Fpn at the translational and posttranslational level is well described, 23 but little is known about transcriptional regulation of Fpn. Previous studies have shown that FPN1 mRNA is increased in vivo in response to iron deficiency anemia and hereditary hemochromatosis 24,25 but is unaffected by dietary iron loading.…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary hemochromatoses are a group of genetic disorders that are characterized by body iron overload due to excessive absorption of dietary iron and resulting organ deposition and subsequent injury [21]. Hepcidin dysregulation (deficiency or resistance) is a common feature among these diseases and can be used to screen for HH in patients with increased ferritin concentrations [22]. Also, it can be used to determine phlebotomy intervals as hepcidin concentrations often return to normal after phlebotomy treatments [23].…”
Section: Inherited Disorders Of Iron Metabolismmentioning
confidence: 99%